The 'epistemological incoherence' of management sciences (1997)
This article describes the dífficulties that management sciences have historically confronted to give epistemological legitimacy to their knowledges, and analyzes their possible contributions to contemporary epistemology. The various attempts to ground management sciences according to positivist precepts reflect an epistemological 'incoherence' which lessens their scientific credibility, but at the same time, in an age of crisis of the positivist paradigm, allows them to participate in the creation of constructivist epistemologies and, in that way, establish new mechanisms of legitimation of their knowledges.